IMPLEMENTASI PENDIDIKAN KARAKTER MELALUI PEMBELAJARAN DALAM MATA PELAJARAN DI SEKOLAH DASAR - Mallawi, Ibadullah (Premiere Educandum, 2013)
Character education has been termed as a process of nurturing values to students to have self-reliance against God, themselves, others, environment and national awareness, which are implemented on their thought, attitude, sense, speech and action based on the norms of religion, law, ethics, culture and custom. Character education at school must involve the stakeholders. The implementation of character education is carried out through launching learning experience which is rooted from building character on students. Character education is integrated classroom practice of all subjects, which can adopt some approaches, one of which is contextual approach bringing real practice in classroom. This approach can hopefully achieve not only cognitive, but also affective and psychomotor skills.Â Keywords: Character Education, Values, Elementary School Classes